Improving Language Ability Through The Method Of Playing With Letters Flashcards Media - Lindawati, Ni Wayan; Permata, Yuni; Widiantana, I Kadek; Monik Rismadewi, Ni Wayan; Gara, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2023)
This study aimed to improve language skills through the method of playing with letter flashcards in group A children at TK Handayani Tiga. This study was conducted as a professional capability strengthening of teachers, which was carried out in two cycles. The subject of professional capability strengthening of teachers was carried out in two cycles. This study consisted of four stages, namely planning, implementing, observing, and reflecting. The subjects of strengthening were the Group A students of TK Handayani Tiga, with 20 children. Data collection in this strengthening was carried out using the technique of playing with picture cards or flashcards while studying. There were also several other techniques, namely conversation, observation, performance, assignments, and work results. The results showed that (1) there was an increase in the average percentage of student learning activeness of 20% (including the criteria of being quite active) in cycle I increased to 60% in cycle II. There was an increase in the percentage of 95%, including moderate criteria. Based on the results, it can be concluded that playing activities with the media of letter flashcards can improve language skills in group A of TK Handayani Tiga.